2020
DOI: 10.1177/0022034520967353
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Promotes the Formation of Preodontoblasts In Vitro

Abstract: Odontoblast differentiation is a complex and multistep process regulated by signaling pathways, including the Wnt/β-catenin signaling pathway. Both positive and negative effects of Wnt/β-catenin signaling on dentinogenesis have been reported, but the underlying mechanisms of these conflicting results are still unclear. To gain a better insight into the role of Wnt/β-catenin in dentinogenesis, we used dental pulp cells from a panel of transgenic mice, in which fluorescent protein expression identifies cells at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…In the present study, BIO treatment enhanced hDPSC osteogenic differentiation, as seen by increased ALP activity, odonto/osteogenic marker gene expression, and mineralised nodule formation. Similar results were found in other cell types, e.g., human PDLSCs [ 59 ], mouse PDLSCs [ 60 ], apical papilla stem cells [ 61 ], mouse DPs [ 62 ], hBMSCs [ 38 ], canine BMSCs [ 46 ], and mouse embryonic fibroblasts [ 63 ]. In contrast, it has been reported that LiCl-mediated Wnt signaling activation decreased the osteogenic differentiation [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, BIO treatment enhanced hDPSC osteogenic differentiation, as seen by increased ALP activity, odonto/osteogenic marker gene expression, and mineralised nodule formation. Similar results were found in other cell types, e.g., human PDLSCs [ 59 ], mouse PDLSCs [ 60 ], apical papilla stem cells [ 61 ], mouse DPs [ 62 ], hBMSCs [ 38 ], canine BMSCs [ 46 ], and mouse embryonic fibroblasts [ 63 ]. In contrast, it has been reported that LiCl-mediated Wnt signaling activation decreased the osteogenic differentiation [ 64 , 65 ].…”
Section: Discussionsupporting
confidence: 78%
“…It was proposed that Alx3 could promote parenchymal and stromal regeneration of tooth tissue by direct transactivation of the Wnt3a and VEGF promoters; thus, the Alx3/Wnt3a axis might represent a pivotal signalling pathway in the regeneration of pulpodentinal complex. Wnt3a was shown to direct and regulate the survival, migration, proliferation, and rapid differentiation of DPSCs [143][144][145]. After infusing recombinant human Wnt3a in collagen gel into clinically treated root canals of miniswine, the regeneration of vascularised pulp-like tissues and mineralised dentin-like structures was observed, probably through the recruitment of endogenous cells and promotion of cell survival in vivo [34].…”
Section: Cell Homing-based Pulp Regenerationmentioning
confidence: 99%
“…These observations indicated that the positive effects of LiCl in the differentiation of osteoblasts and odontoblasts from αSMA + progenitors are mediated by Wnt/βcatenin signaling. The effects of LiCl on early progenitors is very similar to the effects of WNT3a (27).…”
Section: Discussionmentioning
confidence: 67%
“…The LiCl-induced decreases in the levels of Bsp during the mineralization phase of in vitro growth were not reversed by DKK1, indicating that the inhibitory effects of LiCl on osteogenesis and Bsp are not mediated through Wnt/β-catenin signaling. The inhibitory effects of prolonged exposure of pulp cells to LiCl are different from the stimulatory effects of WNT3a on pulp cells (27).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation